2018
DOI: 10.4236/jtr.2018.63018
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Extensively Drug Resistant Tuberculosis (Pre-XDR-TB) among Pulmonary Multidrug Resistant Tuberculosis (MDR-TB) Patients in Bangladesh

Abstract: Background & Objectives: Emergence of drug resistant Tuberculosis (TB) is a major obstacle in the TB control programme of Bangladesh. This study was carried out to detect pre-extensively drug resistant TB (pre-XDR-TB) cases among the multidrug resistant TB (MDR-TB) patients in Bangladesh, as the early detection of pre-XDR-TB can guide clinicians in the appropriate modification of MDR-TB treatment regimen with effective drugs to prevent treatment failure. Methodology: A total of 68 MDR-TB cases were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 6 publications
2
7
2
Order By: Relevance
“…The rate of pre-XDR and XDR-TB in our study were 5.7% and 0.6%, respectively. Compared to our findings, majority of studies reported higher rate of pre-XDR TB in India (56%), China (34%), Pakistan (24%), Bangladesh (16%), Nigeria (17%) and South Africa (17%) [21][22][23][24][25]. The high rate of pre-XDRTB in China, India and other countries compared to our study might be connected to the fact that China and India have the highest rate of MDR-TB in the world and a better laboratory setup and resources for the isolation of drug resistant strains.…”
Section: Discussioncontrasting
confidence: 79%
“…The rate of pre-XDR and XDR-TB in our study were 5.7% and 0.6%, respectively. Compared to our findings, majority of studies reported higher rate of pre-XDR TB in India (56%), China (34%), Pakistan (24%), Bangladesh (16%), Nigeria (17%) and South Africa (17%) [21][22][23][24][25]. The high rate of pre-XDRTB in China, India and other countries compared to our study might be connected to the fact that China and India have the highest rate of MDR-TB in the world and a better laboratory setup and resources for the isolation of drug resistant strains.…”
Section: Discussioncontrasting
confidence: 79%
“…The resistance observed with the drugs could be attributed to the direct alteration of rrs, the shared target via the A1401G mutation is known to confer unequivocal cross-resistance to all three drugs 7 . The prevalence of 20.5% as revealed in this study is similar to studies done in Nigeria, Bangladesh, South Africa and China where the detection of pre-XDR-TB among MDR-TB patients was 21%, 16.2%, 14.0% and 34% respectively [8][9][10][11] . It is also consistent with prevalence of 16.7% reported among MDR TB patients in South Western zone of Nigeria 12 .…”
Section: Discussionsupporting
confidence: 87%
“…Compared to our findings, majority of studies reported higher rate of pre-XDR TB in India (56%), China (34%), Pakistan (24%), Bangladesh (16%), Nigeria (17%) and South Africa (17%). [10][11][12][13][14] The resistance of FQ in our study was 34.44% and it was similar to other several studies, reported as 10%, 13%, 24%, 35% and 57%. [15][16][17][18][19] Data from previous studies suggests that the incidence of FLQ resistant MDR-TB (pre-XDR-TB) is increasing worldwide.…”
Section: Discussionsupporting
confidence: 83%